Anmerkungen zum konzept einer sprachengeographie - Jordan, Peter (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
Language is without any doubt a societal phenomenon, which is in many more ways related to space. While francophone, anglophone and Spanish geography have developed a kind of language geography or geolinguistics as a subdiscipline of geography, geographers in German-speaking countries pay some attention to this fact only within ethnic geography. The paper highlights somemore important spatial aspects of language and proposes to regard language geography as a subdiscipline of cultural geography which has to co-operate closely with linguistics and history.
Keywords: demogeografija; jeziki; nacionalna identiteta; regionalna identiteta